2020
DOI: 10.21203/rs.3.rs-104878/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Quality Analysis Of Low Back Pain Videos On Youtube

Abstract: Background: Most people face low back pain problems at least once in their lifetimes. With the advancing technology, people have been consulting the internet regarding their diagnoses more and more over the last 20 years. This study aims to evaluate the accuracy and reliability of YouTube videos on low back pain. Methods: The keyword “Low Back Pain” was used in our search on YouTube. The first 50 videos to come up in the search results were evaluated using JAMA, DISCERN, and GQS scoring systems. The individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A growing body of literature has found that the quality of YouTube videos on various health issues is low 8–23 . Cardiac Surgery is complex in nature, and the informed consent process is likewise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of literature has found that the quality of YouTube videos on various health issues is low 8–23 . Cardiac Surgery is complex in nature, and the informed consent process is likewise.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature has found that the quality of YouTube videos on various health issues is low. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Cardiac Surgery is complex in nature, and the informed consent process is likewise. Due to COVID-19 related restrictions on access to traditional healthcare, more patients undergoing Cardiac Surgery may be using YouTube for education.…”
mentioning
confidence: 99%